Early Assessment of Response to Radiofrequency Ablation With CT Perfusion Imaging in Rabbit VX2 Liver Tumor Model - Xiaofei Yue (Frontiers Media S.A., 2021)
ObjectivesTo discriminate viable tumors from benign periablational enhancement (BPE) in early stage after radiofrequency ablation (RFA) is a major confounding problem. The goal of this study is to evaluate quantitative assessment and diagnostic value of CT perfusion between viable tumors and BPE after RFA in the rabbit liver VX2 tumor model, with pathological results as the standard.MethodsTwenty-eight VX2 liver tumors were treated with RFA, on days 1, 3, 7, and 14, seven rabbits were randomly chosen for CT perfusion and performed pathology examinations immediately. The perfusion parameters along with the profile of time-density curves (TDCs) and pseudo-color images of the parameters were observed in both BPE and viable tumors, then compared with the pathology results. The perfusion parameters included blood flow (BF), blood volume (BV), time to peak (TTP), permeability (P), arterial liver perfusion (ALP), portal venous perfusion (PVP) and hepatic perfusion index (HPI).ResultsA total of 26/28 rabbits successfully underwent CT perfusion, while 6/26 lesions were confirmed to be viable tumors. The TDCs of BPE were mainly speed-up platform curves (15/26), while the viable tumors showed mainly speed-up speed-down (3/6) and speed-up platform (2/6) curves. The PVP values were significantly higher, and the HPI values were significantly lower for BPE at all time points than viable tumors (P < 0.05). Both of PVP value and HPI value have high efficiency for the differential diagnosis of the viable tumors and BPE at each time point. These characteristics of CT perfusion parameters were consistent with pathological changes.ConclusionsThe TDCs, PVP and HPI have the potential to indicate BPE and viable tumors effectively early after RFA treatment, the results were highly consistent with pathology. CT perfusion has advantages with great efficacy in monitoring the therapeutic effect early after RFA treatment.